Suspended sediment transport in Rio Colorado agricultural basin, Argentina - Cancio, Nicolas C. O.; Pierini, Jorge O. (Frontiers in Built Environment, 2023)
Abstract The contribution of nutrients which comes from the discharge of inland waters,is vital for the development of sea aquatic fauna, being significantly sensitive to the water quality (WQ) changes. The objective of this paper is to evaluate the contribution and distribution of a some parameters of WQ (e.g. nutrients, metals and continental organic compounds) in an indirect way, by the study of the spatiotemporal dynamics of the Cohesive Sediment (CS), this is possible due to CS has a fundamental role in the substances transport by adsorption /desorption interactions. The study area is the Bonaerense Valley of the Colorado River (BVCR) and Argentine Sea, near the mouth of Colorado River (Buenos Aires, Argentina). We use numerical models (MOHID Land and MOHID Water) in a coupled way, evaluating the complex dynamics involved. The parameters evaluated (flow, velocity, cohesive sediment, salinity, and temperature) were calibrated and subsequently validated with data from 7 monitoring stations, located along the Colorado River and adjacent water collectors. The calibration and validation values are within an acceptable range for the purposes , with mean values of 0.8 for NSE (Nash–Sutcliffe model efficiency coefficient), 0.9 (Pearson correlation) for calibration and 0.6 (NSE), 0.9 (Pearson) for validation. The irrigation area (through the collectors) shows a significant contribution of cohesive sediment, of the order of 300 ppm. The river shows approximately 100 ppm and generates a plume along the coast towards northwest.